High-intensity focused ultrasound as a treatment option in renal cell carcinoma. Issue 6 (December 2005) - Häcker, Axel; Dinter, Dietmar; Michel, Maurice Stephan; Alken, Peter
Due to the widespread use of modern imaging modalities, small renal masses are discovered incidentally at increasing rates. Advances in minimally invasive technologies have changed the treatment options for renal cell carcinoma. High-intensity focused ultrasound aims to completely ablate renal tumors in a noninvasive manner. Experimental studies have demonstrated principle feasibility and safety of the technology. However, clinical studies on renal cell carcinoma are very limited and no substantial oncologic results are available to date. Major technical improvements are mandatory to enable high-intensity focused ultrasound as an effective treatment option for patients with small renal masses.